Pueblos arcaicos e Hispania romana. Sistema de castigo y control social - García Falconí , Ramiro J. (2019)
The Roman occupation of the Iberian Peninsula, which began in 218 B.C., and lasted until the fifth century when the Roman Empire fell, not only generated new social and cultural relations, but also affected areas, such as law and, of course, the more violent manifestation of it: criminal law. Although many of the conflicts were resolved under the ancestral customs and habits of the Hispanic people, Roman law has an important influence, as evidenced by the epigraphic sources that are preserved to the present, both in criminal and procedural subjects